Social Justice and Feminist Activism: Writing as an Instrument of Collective Reflection in Prison Spaces - Castillo, Rosalva Aída Hernàndez (Social justice, 2015)
The Life Stories Workshop is important to me because it opens a door to an unknown world that must be considered to eliminate the inequalities we experience in our country. It is also a way to sensitize the hearts in order to create a sisterhood within women of different social classes. In my small space in the female prison area, where different minds, customs and certainties of women inhabit, it is interesting to join our voices and outline life histories, liberating them from this place and making the outside world to know and think about the reality we live in here. This workshop will help achieve women's unity on a shared common goal. It is a way towards mutual support as spokespersons of real stories. Personally, it has allowed me to live a new experience in the world of writing, and feel proud for supporting those who have been silent for too long. My writing will serve those who wish to tell their story. For illiterate women, this workshop has been a means to liberate their story, to unburden themselves on a receptive ear and recover the courage to be a woman that society took away from them. -Testimony of an inmate in the penitentiary newspaper ¿Y ahora que sigue? (2008, 3)